Exploring English Language Teachers’ Challenges and Coping Strategies in Teaching Slow Learners in Inclusive Education Programmes - Khalid, Fathiah Syahirah (IIUM Journal of Educational Studies, 2018)
It has been reported that English as second language (ESL) teachers are not well-trained to teach slow learners in inclusive education. The aim of this study is to explore the challenges that Malaysian English language teachers faced when teaching slow learners in the inclusive educational program as well as to determine their coping strategies. The present study employed a qualitative research method with case study design through face-to-face interviews with three English language teachers from three secondary schools in Malaysia. Five major themes were found through thematic analysis: external factors and internal factors represented the challenges that Malaysian teachers faced when teaching slow learners in the inclusive education, while teaching resources, remedial activities and teachers’ skills represented the coping strategies used by the English language teachers.